Soil Organic Matter Quality in Jatropha spp. Plantations in Different Edaphoclimatic Conditions - Freitas,Rita de Cássia Alves de (2017)
ABSTRACT The substitution of native vegetation by agricultural ecosystems can change the quantity and quality of soil organic matter (SOM), and the intensity of these changes depends on the soil type, climate, and land use. The objective of this study was to evaluate the quality of organic matter in chronosequences of Jatropha cultivation in contrasting soil and climatic conditions. Soil samples were evaluated at depths of 0.00-0.10, 0.20-0.30, and 0.80-1.00 m in chronosequences located in Planaltina, Distrito Federal (Cerrado-Pasture-Jatropha), Dourados, Mato Grosso do Sul (Atlantic Forest-Corn-Jatropha), and Araripina, Pernambuco (Caatinga-Jatropha). To assess SOM quality, we determined C contents in the SOM fractions, C stocks, the carbon management index (CMI), the SOM humification index (HLIF), and the C and N concentrations in the microbial biomass. The conversion of native vegetation to agropastoral systems changed the composition of SOM in the biomes evaluated, especially in the surface layers. The CMI and the C and N contents in the microbial biomass were the most responsive to land use changes in all the biomes studied. The pasture improved SOM quality by increasing the CMI (116) and the C content by 8, 21, and 6 % in the organic, mineral, and organomineral fractions, respectively, while maintaining the SOM humification index and the C and N contents in the microbial biomass in the 0-0.10 m layer. The lowest values of C in the SOM fractions, the CMI (52), and C microbial biomass (136 mg kg-1) were observed for annual crops. Jatropha cultivation increased C contents in the SOM fractions, C stocks, the CMI, and C and N in the microbial biomass with an increase in cultivation time, which demonstrates the potential of this long-term system for improving SOM quality.